2022
DOI: 10.1002/pri.1978
|View full text |Cite
|
Sign up to set email alerts
|

Additional effect of transcutaneous electrical nerve stimulation in a therapeutic exercise program for sedentary with chronic neck pain: A double‐blind randomized controlled trial

Abstract: Purpose To evaluate the additional effect of high frequency (HF) or low frequency (LF) transcutaneous electrical nerve stimulation (TENS) in a specific therapeutic exercise program for the treatment of patients with chronic neck pain. Methods A randomized controlled trial. Sixty participants of both sexes and with chronic neck pain were randomized into three groups: therapeutic exercise group + placebo TENS (n = 20), therapeutic exercise group + HF TENS (n = 20) and therapeutic exercise group + low TENS freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…The 17 studies selected were published between the years 2011 to 2023. The 17 selected studies (Nassif et al, 2011 ; Miyamoto et al, 2013 , 2018 ; Da Luz Junior et al, 2014 ; Vincent et al, 2014 ; Cruz-Díaz et al, 2017 , 2018 ; Keane, 2017 ; Zadro et al, 2019 ; Galan-Martin et al, 2020 ; Tagliaferri et al, 2020 ; Akodu et al, 2021 ; Vicente-Campos et al, 2021 ; Martins de Sousa et al, 2022 ; Cana-Pino et al, 2023 ; Hernandez-Lucas et al, 2023 ; Ogunniran et al, 2023 ) involved 1,354 participants. Variation in chronic non-specific spine-related pain, exercise/physical activity and measures used to assess kinesiophobia contributed to the significant level of heterogeneity between the studies and reported effect estimates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 17 studies selected were published between the years 2011 to 2023. The 17 selected studies (Nassif et al, 2011 ; Miyamoto et al, 2013 , 2018 ; Da Luz Junior et al, 2014 ; Vincent et al, 2014 ; Cruz-Díaz et al, 2017 , 2018 ; Keane, 2017 ; Zadro et al, 2019 ; Galan-Martin et al, 2020 ; Tagliaferri et al, 2020 ; Akodu et al, 2021 ; Vicente-Campos et al, 2021 ; Martins de Sousa et al, 2022 ; Cana-Pino et al, 2023 ; Hernandez-Lucas et al, 2023 ; Ogunniran et al, 2023 ) involved 1,354 participants. Variation in chronic non-specific spine-related pain, exercise/physical activity and measures used to assess kinesiophobia contributed to the significant level of heterogeneity between the studies and reported effect estimates.…”
Section: Resultsmentioning
confidence: 99%
“…This was largely because of blinding, allocation sequence concealment and deviation from intended intervention. Five studies (Nassif et al, 2011 ; Miyamoto et al, 2013 , 2018 ; Zadro et al, 2019 ; Galan-Martin et al, 2020 ) were rated as having high risk of risk, ten (Vincent et al, 2014 ; Keane, 2017 ; Cruz-Díaz et al, 2018 ; Tagliaferri et al, 2020 ; Akodu et al, 2021 ; Vicente-Campos et al, 2021 ; Martins de Sousa et al, 2022 ; Cana-Pino et al, 2023 ; Hernandez-Lucas et al, 2023 ; Ogunniran et al, 2023 ) with some concerns of bias and two (Da Luz Junior et al, 2014 ; Cruz-Díaz et al, 2017 ) deemed low risk. Most studies adequately described the follow-up period, but attrition rate was poorly defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations